Convict Depot - (:unkn) unknown (Waterman, the Hatter, Clothier and Outfitter,[Trinidad and Tobago], 2011)
The postcard shows Carrera Island, referred to as Convict Depot because during the 1800s prisoners were carried to the island to quarry limestone for road building. In 1877, a prison was constructed, today the island remains a prison island.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Prisons--Trinidad and Tobago; Islands--Trinidad and Tobago; Carrera Island